The impact of ergometer design on hip and trunk muscle activity patterns in elite rowers: An electromyographic assessment - Nowicky, A. V.; Burdett, R.; Horne, S. (Journal of Sports Science & Medicine, 2005)
This study used surface electromyography (sEMG) to examine whether there were differences in hip and trunk muscle activation during the rowing cycle on two of the most widely used air braked ergometers: the Concept 2C and the Rowperfect. sEMG methods were used to record the muscle activity patterns from the right: m. Erector spinae (ES), m. Rectus Abdominus (RA), m. Rectus Femoris (RF) and m. Biceps Femoris (BF) for their contributions as agonist-antagonist pairs underlying hip and trunk extension/flexion. The sEMG activity patterns of these muscles were examined in six young male elite rowers completing a 2 minute set at a moderate training intensity (23 stroke·min-1 and 1:47.500 m-1 split time, 300W). The rowers closely maintained the required target pace through visual inspection of the standard LCD display of each ergometer. The measurements of duration of each rowing cycle and onset of each stroke during the test were recorded simultaneously with the sEMG activity through the additional instrumentation of a foot-pressure switch and handle accelerometry. There were no significant differences between the two ergometer designs in group means for: work rate (i.e., rowing speed and stroke rate), metabolic load as measured by mean heart rate, rowing cycle duration, or timing of the stroke in the cycle. 2-D motion analysis of hip and knee motion for the rowing cycle from the video footage taken during the test also revealed no significant differences in the joint range of motion between the ergometers. Ensemble average sEMG activity profiles based on 30+ strokes were obtained for each participant and normalised per 10% intervals of the cycle duration as well as for peak mean sEMG amplitude for each muscle. A repeated measures ANOVA on the sEMG activity per 10% interval for the four muscles contributing to hip and trunk motion during the rowing cycle revealed no significant differences between the Concept 2C and Rowperfect (F = 0.070, df = 1,5, p = 0.802). The outcome of this study suggests that the two different ergometer designs are equally useful for dry land training.